Parasitic Effect of Tube Wall Longitudinal Heat Conduction on Cryogenic Gas Temperature - A. Saberimoghaddam; M. M Bahri Rasht Abadi (Iranian Journal of Chemical Engineering)
Longitudinal heat conduction is an important parameter in the cryogenic field, especially in cryogenic heat exchangers. In the present work, the parasitic effect of tube wall longitudinal heat conduction on temperature measurement has been studied in cryogenic laminar hydrogen flow. The effects of various parameters such as wall cold end temperature, wall thermal conductivity, gas volumetric flow, and tube wall thickness have been investigated by finite element method. The model was also validated versus the data obtained from experiments. The simulations showed that the temperature decrease in gas flow occurs in the end section of tube length. This section is independent of tube cold end temperature and causes for large temperature measurement error in laminar flows. Results showed that a few millimeters change in temperature sensor position results in measurement errors up to 80 %. The higher tube wall thermal conductivity and tube wall thickness result in higher parasitic effects of longitudinal heat conduction.